2017
DOI: 10.1021/acsami.7b06705
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of Microfibrillar Crystalline Superstructure: Achieving High-Performance Polylactide

Abstract: As a biobased and biodegradable polyester, polylactide (PLA) is widely applied in disposable products, biomedical devices, and textiles. Nevertheless, due to its inherent brittleness and inferior strength, simultaneously reinforcing and toughening of PLA without sacrificing its biodegradability is highly desirable. In this work, a robust assembly consisting of compact and well-ordered microfibrillar crystalline superstructure (FCS) surrounded by slightly oriented amorphism, is achieved by a combined external f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 66 publications
(117 reference statements)
3
50
0
Order By: Relevance
“…On the one hand, the microfibrils movement and slippage during the spinning process resulted in pore collapsed, which was contributed to decrease the content of the pore defects and surface defects. Therefore, it might reduce the probability of the stress accumulation and crack formation under load; on the other hand, served as the self‐reinforcement in PAN fibers, closely interlinked fibrils could efficiently resist the cracks propagation and dissipate the much energy . Consequently, the PAN precursor fibers with the homogeneous, compact, well‐oriented, and closely interlinked fibrils, presented high tensile strength and initial modulus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the microfibrils movement and slippage during the spinning process resulted in pore collapsed, which was contributed to decrease the content of the pore defects and surface defects. Therefore, it might reduce the probability of the stress accumulation and crack formation under load; on the other hand, served as the self‐reinforcement in PAN fibers, closely interlinked fibrils could efficiently resist the cracks propagation and dissipate the much energy . Consequently, the PAN precursor fibers with the homogeneous, compact, well‐oriented, and closely interlinked fibrils, presented high tensile strength and initial modulus.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 23,24 combined the ultrasonic breakup and solvent etching to separate the fibril elements from PAN fibers and proposed the formation process of the periodic lamellae structures in microfibrils. Li et al 25 suggested that the fibrils served as the self-reinforcing elements to enhance the material mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] This technology can forcibly assemble one or more polymers into a film with a multilayered structure, where the thickness and number of layers can be effectively regulated by related parameters such as the multiplying elements, extrusion rate, and stretch rate. [27][28][29] Each layer is constructed in a unique 2D confined space. [30,31] By changing the size of this 2D confined space, a multilayered film will exhibit improved compatibility, conductive and thermal barriers, and rheological and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanolayer coextrusion is a novel technology that can produce a polymer film with a special multilayered structure . This technology can forcibly assemble one or more polymers into a film with a multilayered structure, where the thickness and number of layers can be effectively regulated by related parameters such as the multiplying elements, extrusion rate, and stretch rate . Each layer is constructed in a unique 2D confined space .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high aspect ratio would supply a stronger shear stress. Stronger shear stress leaded to a stronger shear‐induced orientation of polymer chains and fillers in polymer composites , which had unique advantages in the field of the crystallization behavior of polymer chains and the dispersion and orientation of fillers , but might worsen the interface deformations. For example, we designed a rectangle LME with a higher aspect ratio of 20:1 at the outlet, the schematic of which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%